Analisis Reaksi Pasar Modal terhadap Groundbreaking Ibu Kota Negara (IKN) pada Saham Perusahaan Sektor Properti dan Konstruksi di Bursa Efek Indonesia - Billy Alberto; Tona Aurora Lubis; Fitriaty Fitriaty (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the capital market reaction to the groundbreaking event of the new capital city (IKN) on the stock prices of property and construction sector companies listed on the Indonesia Stock Exchange (IDX). This research employs a quantitative approach using the event study method with an observation period of 11 days, consisting of 5 days before (t-5), the event day (t), and 5 days after (t+5) the event. The sample includes property and construction sector companies that were actively traded during the observation period. Data analysis was conducted using the Paired Sample t-test through SPSS to examine differences in Abnormal Return (AR), Cumulative Abnormal Return (CAR), and Trading Volume Activity (TVA) before and after the event. The results show that there is no significant difference in AR and TVA, but there is a significant difference in CAR, indicating that the market reacted cumulatively to the groundbreaking IKN information. These findings support the semi-strong form of market efficiency theory, suggesting that the market requires time to fully reflect information into stock prices.